IDENTIFIKASI RESERVOAR HIDROKARBON MENGGUNAKAN METODE AVO DAN INVERSI BERBASIS MODEL PADA LAPANGAN âSANGATâ - , RUDI CAHYONO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study uses the AVO analysis method and acoustic impedance inversion to identify the physical properties of the reservoir on the 3D seismic data in the Field \"SANGAT\", Talang Akar Formation, South Sumatra Basin. Talang Akar formation is one of the formations containing hydrocarbon reservoir, compiled by sandstones intersecting shalestone . Input data in this study is the 3D seismic data Pre Stack Time Migration (PSTM) in the form of CDP Gather and well log data. CDP Gather is processed into angel gather for AVO analysis that generates AVO attributes : Product, Scale Poisson 's Ratio Charged and Fluid factor. Angel gather in - full stack Stack produces CDP stack for acoustic impedance seismic inversion. The analysis results of log sensitivity shows that the target reservoir at Talang Akar Formation is sandstones \"A\" which has a values range below 80 API Gamma Ray and 12-24% Nuetron porosity. The result acoustic impedance inversion indicates that the values range of acoustic impedance on sandstone reservoir is known for 7000-8900 ((m/s)(g/cc)), density values 2.23-2.4 (g/cc) and 3100-3500 (m/s) P wave velocity. The analysis Results of acoustic impedance, apparent density and P-wave velocity slice shows that there are three zones of hydrocarbon prospects namely Zone A, Zone B and Zone C.